Virgin Coconut Oil in Ketogenic Diet - Silalahi, Jansen; Silalahi, Yosy C E (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
A ketogenic diet consists of high fat, with moderate to low protein content, and very low carbohydrates, which forces the body to use fat instead of glucose to produce energy which is called ketosis. Ketogenic diets are commonly used in patients suffering from neurological disorders, and mostly epilepsy. Fat is a mixture of different triacylglycerol molecules formed by esterification of glycerol with three fatty acids. Based on the length of fatty acids in triacylglycerols, fats and oils can be classified into two groups; medium chain triglycerides composed of short and medium chain fatty acids containing 4 to 12 carbon atom, and long chain triglycerides composed of long chain fatty acids containing 14 to 22 carbon. Metabolism of medium chain triglycerides is different from that of long chain triglycerides. Classic or old ketogenic diet use long chain triglycerides as fat component may cause side effects such as dislipidemia and hence increase cardiovascular disease risk.This drawback may be reduced by replacing long chain triglycerides with medium chain triglycerides. Coconut oil belongs to medium chain triglyceride fats because it’s fatty acids consist mostly of medium chain fatty acids. There are two kinds of coconut oil obtained from coconut meat namely coconut oil used for frying, and virgin coconut oil is directly consumable and more suitable in Ketogenic diets